MODULATORY EFFECT OF POLYMER TYPE AND CONCENTRATION ON DRUG RELEASE FROM SUSTAINED RELEASE MATRIX TABLETS OF RANOLAZINE: A COMPARATIVE RELEASE KINETIC STUDY - M AGIBA, AHMED; HAKEEM, WAGEEH ABDEL; G ZAYED, ASHRAF (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Ranolazine (RZ), antianginal drug indicated for the treatment of chronic stable angina pectoris, was formulated into sustained-release matrix tablets and optimized to improve patient compliance and achieve controlled release over a certain period. Methods: Different formulations were prepared by wet- and melt-granulation techniques. Excipients at different ratios as Eudragit® L100-55, Methocel™ E5, Avicel® PH-101, and carnauba wax powder were used to develop a ternary polymeric matrix system for the controlled delivery of RZ. The prepared formulations were subjected to granulometric and characteristic studies. Comparative dissolution and release kinetic studies of the selected formulation and the reference product, Ranexa® extended-release film-coated tablets, Gilead Sciences, Inc., USA, were further carried out to ensure product similarity. Results: The optimum pH-dependent to pH-independent polymers ratio was 1:1.3 (w/w). Extragranular carnauba wax in a concentration of 32.50 mg/tablet (2.50 gm% w/w) was the key excipient in controlling drug release kinetics by forming waxy matrix granules which prevent rapid dissolution. Modulation of the microenvironmental pH using a potent alkalinizing agent was very effective for controlling drug release patterns in different dissolution media from pH 1.2–6.8. Conclusion: The release of RZ from the matrix tablets was controlled for a period of 24 h, and thereby expected to provide patient compliance with minimal side effects.